BRIKET ARANG KULIT KACANG TANAH DENGAN PROSES KARBONISASI - Retno Dewati, Rezy Putri Ragilia, Tieka Kharisma 2), Kindriari Nurma Wahyusi 1) (Jurnal Teknik Kimia, 2012)
The Peanuts peel can be converted to charcoal through  the carbonization process with tapioca moulded as adhesive. Making  briquettes from peanut peel is usefull as an alternative fuel. Peanut peel were cutted in two parts and dried in open air.  Next, it were carbonized in 200 0C, 225 0C, 250 0C, 275 0C and 300 0C and 300 0C for 90 minutes. Then the charcoal ware pounded and sieved to make it in uniform size (40 mesh). Then it was weighed in 25 grams, 50 grams, 75 grams, 100 grams and 125 grams. And then mixed with adhesive moulded. The moulded briquettes were dried through the air for 24 hours and then it were heated in the oven with 100 0C for 1 hour. Then the briquettes were analyzed calorific value, ash content, water content and color of flame. Finally, the highest calorific value of charcoal briquettes was on the composition of peanut peel 75 grams and 250 0C, it give 6536.98 kcal / kg. The lowest water content in the composition of 125 grams and 300 0C, it give 2,014%.  And the lowest ash content generated in the composition of 75 grams and 200 0C, it give 7,39%. Key words : Carbonization, Charcoal Briquette, moulded, peanut skin,